Carer burden and dyadic attachment orientations in adult children-older parent dyads. (September 2020) - Romano, Daniel; Karantzas, Gery C.; Marshall, Emma M.; Simpson, Jeffry A.; Feeney, Judith A.; McCabe, Marita P.; Lee, Juwon; Mullins, Ellie R.
Highlights: Anxious-avoidant attachment pairings predict increased burden in adult-child carers. Similar attachment insecurity in parent-child dyads do not predict burden. Taking a dyadic approach to examining attachment in ageing families is critical. Abstract: Background and Objectives: This study takes an interpersonal approach to the study of carer burden in families where adult children care for older parents. The aim of the study was to determine whether different pairings of attachment insecurity in older parent-adult child dyads are predictive of carer burden. Research Design and Methods: Seventy dyads whereby adult children provided weekly care to their older parents completed self-report measures of attachment. Adult children also completed a measure of carer burden. Results: Anxious-avoidant attachment insecurity pairings in parent-child dyads were associated with increases in carer burden. However, anxious-anxious and avoidant-avoidant attachment insecurity pairings were not associated with burden. Discussion and Implications: The attachment insecurity of the care-recipient was found to moderate the association between a carer's attachment insecurity and burden, but only when the care-recipient's attachment insecurity differed to that of the carer's. These findings have implications for research, policy, and practice in aged care. The findings highlight the importance of focusing on attachment insecurity in aging families as well as taking a dyadic perspective when studying caregiving outcomes such as carer burden. The findings suggest that carers who may require the greatest support are those whose parents demonstrate contrasting orientations of attachment insecurity.